Heavy metal spatial and temporal trends (2008–2018) in clams and mussel from Adriatic Sea (Italy): Possible definition of forecasting models. (February 2021) - Tavoloni, Tamara; Miniero, Roberto; Bacchiocchi, Simone; Brambilla, Gianfranco; Ciriaci, Martina; Griffoni, Francesco; Palombo, Paolo; Stecconi, Tommaso; Stramenga, Arianna; Piersanti, Arianna
Abstract: In 2008–2018, 1458 georeferenced samples of clams and 343 of mussels were harvested in Italy from classified areas along Marche coast and analyzed within food-safety monitoring plans. Pb, Cd, V, Ni, Cr, and As median levels (mg kg −1 ) were 0.09, 0.08, 0.29, 0.77, 0.35, and 2.35 in clams and 0.16, 0.15, 0.46, 0.48, 0.25, and 3.34 in mussels. The reported levels were comparable with the published ones, and Hg always fell below LOQ (0.025 mg kg −1 ). Pb and Cd datasets, based on quarterly results, show a decreasing trend in clams and constant baseline value for mussels. Time-trends and forecasting models represent an asset to predict emerging food safety/security risks. The metal levels in mussels and clams from the same area allow environmental safety assessment and thus enable the evaluation of contaminants in both water column and sediment. Monitoring of elements that are not regulated may help in preserving food and environmental safety. Graphical abstract: Unlabelled Image Highlights: 2008–2018 clams and mussels monitoring results (Central Adriatic coast - Italy). Pb, Cd, Hg (regulated), As, Cr, V, Ni (not regulated) in 1458 clams and 343 mussels Pb, Cd time trends analysis yielding risk prioritization in monitoring plans. Cd and Pb in clams showed a decreasing trend, mussels a fluctuating constant level. Highest heavy metals levels were found in Ancona, significantly anthropized area.